2017
DOI: 10.1002/admi.201700007
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hysteresis Effects in Organohalide Perovskite Solar Cells

Abstract: Thin‐film solar cell based on hybrid perovskites shows excellent light‐to‐power conversion efficiencies exceeding 22%. However, the mixed ionic‐electronic semiconductor hybrid perovskite exhibits many unusual properties such as slow photocurrent instabilities, hysteresis behavior, and low‐frequency giant capacitance, which still question us so far. This study presents a direct surface functionalization of transparent conductive oxide electrode with an ultrathin ≈2 nm thick phosphonic acid based mixed C60/organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 52 publications
3
77
0
Order By: Relevance
“…Between TiO 2 and perovskite an ultrathin SAM (self‐assembled monolayer) was inserted to reduce the hysteresis. As can be seen in Figure , hysteresis disappears by insertion of a C 60 ‐based SAM between TiO 2 and MAPbI 3 in normal planar structure . Impedance studies revealed that capacitance of the C 60 ‐SAM‐based devices showed about two orders of magnitude smaller at low and medium frequencies than that of the TiO 2 ‐based devices, which underlines that ionic defect density at interface was significantly reduced by insertion of interlayer.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Between TiO 2 and perovskite an ultrathin SAM (self‐assembled monolayer) was inserted to reduce the hysteresis. As can be seen in Figure , hysteresis disappears by insertion of a C 60 ‐based SAM between TiO 2 and MAPbI 3 in normal planar structure . Impedance studies revealed that capacitance of the C 60 ‐SAM‐based devices showed about two orders of magnitude smaller at low and medium frequencies than that of the TiO 2 ‐based devices, which underlines that ionic defect density at interface was significantly reduced by insertion of interlayer.…”
Section: Introductionmentioning
confidence: 83%
“…In normal structure, TiO 2 and spiro‐MeOTAD are chosen for investigation because they were mostly employed for PSCs. Figure shows some of selected J – V curves of the device employing MAPbI 3 in normal mesoscopic device structure including c‐TiO 2 , mp‐TiO 2 . Although kink structure of the forward scanned J – V curves and small deviation in V oc are sometimes detected, almost no change in J sc and V oc between reverse and forward scan is observed as common feature in the normal mesoscopic structure of FTO/c‐TiO 2 /mp‐TiO 2 /MAPbI 3 /spiro‐MeOTAD/Au.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Research on different interfacial organic modifiers has gained attention due to their ability to influence oxide properties, tune their electrical, chemical, and physical properties, affect charge carrier dynamics (transport, injection, and recombination) or modify their work function. Other benefits of applying surface modifiers in PSCs are, for example, the enhancement of moisture tolerance, the suppression of hysteresis, the enhancement of power conversion efficiency, and lifetime stability; moreover, the enhancement of the fracture resistance of perovskite films can be reinforced with the aid of organic or polymeric modifiers …”
Section: Introductionmentioning
confidence: 99%